2007
DOI: 10.1590/s0004-27492007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Transplante de córnea em ceratocone: avaliação dos resultados e complicações obtidos por cirurgiões experientes e em treinamento

Abstract: In a corneal referral practice, the visual results after PK were similar to those related to the PK performed by either expert surgeons or in training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…However, although corneal transplantation is the oldest, most common and most successful form of tissue transplantation, due to the immunological privilege of the anterior chamber, rejection continues to be the biggest cause of failure in corneal transplants, even considering non-vascularised corneas such as keratoconus [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, although corneal transplantation is the oldest, most common and most successful form of tissue transplantation, due to the immunological privilege of the anterior chamber, rejection continues to be the biggest cause of failure in corneal transplants, even considering non-vascularised corneas such as keratoconus [21].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment is reserved for cases when contact lenses can no longer be fitted, become intolerable or do not provide good visual acuity (12) . Alternative surgical techniques, such as the implantation of ICRS have been developed to try to avoid or postpone penetrating keratoplasties (13) .…”
Section: Introductionmentioning
confidence: 99%
“… 3 4 Many studies have reported the outcomes of penetrating keratoplasty procedures performed by residents during elective surgery in the OR. 5 6 7 8 9 10 11 However, a large diversity of assessment parameters has been proposed (i.e., details on surgery times, graft clarity, postoperative astigmatism, best corrected visual acuity, and graft survival), reflecting the difficulty of finding widely accepted and reproducible assessments for the quality of a given surgical procedure. Defining the optimal parameters for assessing good surgical procedures remains difficult, 12 and the corresponding objective scores for their assessment in corneal suturing still need to be determined.…”
mentioning
confidence: 99%